[OP.1C.10] BENEFITS OF AMBULATORY BLOOD PRESSURE MEASUREMENT IN POST ACUTE AORTIC SYNDROME: PREDICTORS FOR BLOOD PRESSURE CONTROL AND IMPORTANCE OF NOCTURNAL BLOOD PRESSURE INFLUENCE. (September 2016) - Delsart, P.; Ledieu, G.; Devos, P.; Sobocinski, J.; Clough, R.; Haulon, S.; Mounier-Vehier, C.
Abstract : Objective: Ambulatory blood pressure measurement (ABPM) is recommended to assess optimal blood pressure (BP) control, the most important factor in management post acute aortic syndrome (AAS). Data in this case are lacking. ABPM has previously been shown to be more closely associated with prognosis than clinical values. We assessed these advantages in post AAS. Figure. No caption available. Design and method: We retrospectively collected data from 111 patients with Type B AAS from January 2004 to September 2014. Controlled BP group was defined according to a 24-h BP under 130/80 mmHg. The follow-up began at discharge. Results: The population consisted of 85 males, with a mean age of 60.9+/−12.9 years and a mean body mass index of 28.4 +/−6.2 Kg/m 2 . The mean delay between ABPM and AAS was 4.4 +/−10.2 months. The mean 24-h BP of the entire population was 123.9/71 +/−15.2/8.8 mmHg. BP was not controlled in 41 patients (36.9%). The treatment score at discharge was 3.9+/−1.4. There was no difference between groups regarding the class of antihypertensive drugs. The mean glomerular filtration rate was 83.3 +/−28.5 mL/mn/1.73 m 2, with no difference between groups. Peripheral stent implantation in the acute phase (OR = 3.857 [1.199–12.406], p = 0.023), higher left ventricular ejection fraction (OR = 1.092 [1.005–1.187], p = 0.038) and higher platelet count at discharge (OR = 1.064 [1.018–1.112], p = 0.006) were identified as predictors of good BP control by multivariate analysis. There was no difference between groups regarding the incidence of aortic intervention. Prognostic analysis to identify predictors of mortality, cardiovascular event, or aortic event during follow-up showed night-time systolic BP was associated with aortic events at follow-up (HR = 1.017 [1–1.034], p = 0.0486), particularly for a threshold of 124 mmHg or more (HR = 1.967 [1.052–3.678], p = 0.0341). Conclusions: ABPM could be useful in the management of patients post AAS. Peripheral revascularization to prevent malperfusion improves BP control and therefore offers a new method in the early phase management of ASS. Night-time systolic BP has a significant effect on the incidence of aortic events during follow-up.